IMPLEMENTATION OF CHARACTER EDUCATION IN INDONESIAN LEARNING AT SMA NEGERI 2 TOLITOLI - Sudaryati, Sri (Jurnal Madako Education, 2021)
This study aims to describe the implementation of character education in Indonesian language learning. This research is a descriptive study with a qualitative approach. The subjects of this study were Indonesian language teachers at SMA Negeri 2 Tolitoli. Data collection was obtained from the results of document analysis interviews, and through observations. The analysis to determine the results of the study is according to the problems in the research. Data collection was obtained from the results of document analysis interviews, and through observations.